TRANSFORMASI SOSIAL DI ERA DIGITAL DALAM PERSPEKTIF AL-QURAN: KAJIAN LITERATUR TENTANG MORAL DAN ETIKA INTERAKSI SOSIAL - Loso Judijanto; Syafril Barus (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
This research explores social transformation in the digital age from a Qur'anic perspective, focusing on the morals and ethics of social interaction. In the digital age, major changes are taking place in the way humans communicate and interact, which often pose new challenges in maintaining integrity, trust and harmonious social relationships. Based on a comprehensive literature review, this study highlights how the values taught in the Qur'an, such as honesty, trust, empathy and balance, are important guidelines for adapting to the digital world. Through this analysis, this study provides insights into the importance of moral and ethical awareness in utilising digital technology, as well as how spiritual values can strengthen social bonds and avoid negative impacts that have the potential to undermine social and moral order